The unrecognized importance of carbon stocks and fluxes from swamps in Canada and the USA - Scott J Davidson; Emily Dazé; Eunji Byun; Dean Hiler; Markus Kangur; Julie Talbot; Sarah A Finkelstein; Maria Strack (Environmental Research Letters, 2022)
Swamps are a highly significant wetland type in North America both in terms of areal extent and their role in terrestrial carbon cycling. These wetlands, characterized by woody vegetation cover, encompass a diverse suite of ecosystems, including broad-leaved, needle-leaved, mixedwood or shrub/thicket swamps. Uncertainties in the role of swamps in carbon uptake and release continue to be substantial due to insufficient data on variabilities in carbon densities across diverse swamp types and relatively few flux measurements from swamp sites. Robust measurements of rates of vertical accretion of swamp soils and the associated long-term rates of carbon accumulation, alongside measurements of carbon losses from swamps, are needed for emerging frameworks for carbon accounting, and for assessments of the impacts of climate warming and land use change on this important wetland type. Based on data compilation, we present here a comparative analysis from a series of North American swamp sites on carbon dioxide, methane and dissolved organic carbon fluxes, aboveground biomass, net primary productivity (NPP), and soil carbon properties including bulk densities, organic carbon contents, peat depths, rates of vertical accretion, and rates of long-term carbon accumulation. We compare these properties for four major swamp types: needle-leaved, broad-leaved, mixedwood and shrub/thicket swamps. We show differences in carbon fluxes, biomass and NPP across the four types, with broad-leaved swamps having the largest CH _4 flux, highest soil bulk densities, thinnest peat depths and lowest soil organic matter contents, whereas needle-leaved swamps have the smallest CH _4 flux, highest aboveground biomass and highest NPP. We show high soil carbon stocks (kg C m ^−2 ) in all types of swamps, even those where organic deposits were too shallow to meet the definition of peat. However, we note there is a significant lack of studies focused on swamp carbon dynamics despite their abundance across Canada and the United States.